2013
DOI: 10.1530/joe-12-0304
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthyroidism causes cardiac dysfunction by mitochondrial impairment and energy depletion

Abstract: This study elucidates the role of metabolic remodeling in cardiac dysfunction induced by hyperthyroidism. Cardiac hypertrophy, structural remodeling, and expression of the genes associated with fatty acid metabolism were examined in rats treated with triiodothyronine (T 3 ) alone (8 mg/100 g body weight (BW), i.p.) for 15 days or along with a peroxisome proliferator-activated receptor alpha agonist bezafibrate (Bzf; 30 mg/100 g BW, oral) and were found to improve in the Bzf co-treated condition. Ultrastructure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 49 publications
1
22
0
4
Order By: Relevance
“…Even low-normal free thyroxin levels in patients with euthyroidism have been associated with insulin resistance (22,23). Thyroid disease induces mitochondrial dysfunction (24)(25)(26)(27), and statins reduce levels of coenzyme Q10, a component of the electron transport chain involved in the process of ATP generation (28), also leading to mitochondrial dysfunction as well as causing reduced insulin release and pancreatic b-cell failure and contributing to the development of DM (29)(30)(31)(32). Downregulation of GLUT4 in adipocytes has also been shown to be a result of statin treatment, an effect that has been explained in terms of reduced isoprenoid biosynthesis (33).…”
Section: Discussionmentioning
confidence: 99%
“…Even low-normal free thyroxin levels in patients with euthyroidism have been associated with insulin resistance (22,23). Thyroid disease induces mitochondrial dysfunction (24)(25)(26)(27), and statins reduce levels of coenzyme Q10, a component of the electron transport chain involved in the process of ATP generation (28), also leading to mitochondrial dysfunction as well as causing reduced insulin release and pancreatic b-cell failure and contributing to the development of DM (29)(30)(31)(32). Downregulation of GLUT4 in adipocytes has also been shown to be a result of statin treatment, an effect that has been explained in terms of reduced isoprenoid biosynthesis (33).…”
Section: Discussionmentioning
confidence: 99%
“…However, Maity et al [12] have shown that after 5-8 days in the rat these begin to diminish. Heart failure in hyperthyroidism is well known, even without atrial fibrillation and disproportionate tachycardia.…”
Section: Some Paradigms Should Be Givenmentioning
confidence: 96%
“…Additionally, Maity et al [12] showed that ATP is increased very early (day 2) in the rat decreasing progressively from day 5 to 15. The rats received 8 μg/100 µg BW ip for 15 days.…”
Section: Some Paradigms Should Be Givenmentioning
confidence: 99%
See 2 more Smart Citations